HUBUNGAN USIA MENARCHE, LAMA MENSTRUASI DAN STATUS GIZI DENGAN KEJADIAN DISMINORE PADA SISWI SMA PUSPITA CINTA MANIS BARU BULAN MARET TAHUN 2024 - Mutmainah, Vepti Triana; Nitya Culodia, Ni Wayah (Jurnal Ilmiah Kesehatan BPI, 2025)
Dysmenorrhea is abdominal pain originating from uterine cramps during menstruation. The pain emerges concurrently with the onset of menstruation and lasts for several hours to several days until it reaches its peak. According to the World Health Organization (WHO), there is the prevalence of 1,769,425 cases (90%) of women experiencing dysmenorrhea, of which 10-15% suffer from severedysmenorrhea. This is supported by research conducted in various countries with astonishing results, where the occurrence of primary dysmenorrhea in each countryis reported to be more than 50%. The purpose of this study was to determine the relationship of age at menarche, menstrual period, nutritional status to the occurrence of dysmenorrhea in female students of senior high school. Thiswas an analytical survey with a cross-sectional approach, involving 33 students. The data were analyzed by using the Chi-Square statistical test. The results of univariate analysis showed that 54.5% of the students experienced dysmenorrhea and 45.5% did not; 36.4% had abnormal age at menarche and 63.6% had normal age at menarche; 45.5% had abnormal menstrual period and 54.3% had normal menstrual period; as for nutritional status, 42.4% fell under the abnormal category and 57.6% under the normal category. The results of bivariate analysis showed a significant relationship. A significant relationship was found between age at menarche and the occurrence of dysmenorrhea, with the p-value of 0.032. A significant relationship also existed between menstrual period and the occurrence of dysmenorrhea, with the p-value of 0.002. Furthermore, a significant relationshipwas identified between nutritional status and the occurrence of dysmenorrhea, withthe p- value of 0.043. It is recommended that healthcare workers should provide and improve health counseling on dysmenorrhea.